Environmental Critical Aspects of The Conversion of Biomass to Biogas for Sustainable Energy in Indonesia - Rame Rame; Purwanto Purwanto; Sudarno Sudarno (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2021)
Renewable energy will become the foundation for meeting the world's energy needs in the future. However, Indonesia has not done much research on the development and application of technology for sustainable energy. Indonesia has potential energy sources. However, biomass conversion into other forms of energy, such as biogas, will hurt the environment. The development of biomass-based bioenergy is one of the best solution for meeting Indonesia's current and future energy needs. Biogas is biomass-based bioenergy, which is the potential for future energy sources. Minimizing the environment's degradation is a significant aspect of preparing the biomass to biogas conversion model. Furthermore, the production of biogas with automatic monitoring and control will minimize new waste formation. Indonesian government regulatory support and total community participation will increase converting biomass into biogas as renewable energy into electrical energy. The paper analyzes the environmental impact of biomass conversion into biogas and proposed an environmentally friendly conversion model.